ANALISIS PERTUMBUHAN EKONOMI KOTA MEDAN DENGAN PENDEKATAN ERROR CORRECTION MODEL (ECM) - Anton Atno Parluhutan Sinaga; Selamat Siregar (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2016)
Â Economic growth is one of the important indicators in the analysis of the economic development that occurs in a country or region. Economic growth is the process whereby an increase in real gross national product or national income real. The purpose of this study was to determine whether the inflation, interest rates and exchange rates affect economic growth in the short term and long term in the city of Medan. Samples taken include data on inflation, Â Interest Rate, exchange rate, Economic Growth Medan City Year 2000-2015. The analysis tool used is the Engle-Granger Error Correction Model (EG-ECM). Data processing is done electronically ie using Eviews Software 7.0The research results in the short term is the variable interest rate and exchange rate SBI has a significant influence on the economic growth of the city of Medan. While the inflation variable does not have a significant impact on economic growth in the city of Medan. In the variable length SBI inflation and interest rates have a significant influence on the economic growth of the city of Medan. While the variable rate has no significant effect on economic growth in the city of Medan. The magnitude of the influence of the independent variables of inflation, SBI interest rate and the exchange rate against the growth of the city of Medan in the short term by 42.64% and for the long term at 66.74 and the rest describe the influence of variables outside the model.